2016
DOI: 10.3390/ijerph13060609
|View full text |Cite
|
Sign up to set email alerts
|

Crash Frequency Modeling Using Real-Time Environmental and Traffic Data and Unbalanced Panel Data Models

Abstract: Traffic and environmental conditions (e.g., weather conditions), which frequently change with time, have a significant impact on crash occurrence. Traditional crash frequency models with large temporal scales and aggregated variables are not sufficient to capture the time-varying nature of driving environmental factors, causing significant loss of critical information on crash frequency modeling. This paper aims at developing crash frequency models with refined temporal scales for complex driving environments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…Given the criticism against ZINB in safety studies, the present study develops random effect hurdle negative binomial and Poisson models to study crash frequency on fine time scales as a complementary study to our prior research [26]. Firstly, random effect models including REHNB, REHP, RENB and REP are established to study the daily crash frequency with the panel data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the criticism against ZINB in safety studies, the present study develops random effect hurdle negative binomial and Poisson models to study crash frequency on fine time scales as a complementary study to our prior research [26]. Firstly, random effect models including REHNB, REHP, RENB and REP are established to study the daily crash frequency with the panel data.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by the authors examined hourly crash frequency using the ZINB model and showed that ZINB is capable of addressing preponderance zeroes in crash data [26]. However, zero-inflated models used for crash prediction also received some criticisms because of the structural-zero assumption [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…This system has a separate right of way, which has no influence on the current ground transportation system. In the case of crowed urban space and traffic congestion on the road system, it can effectively alleviate traffic pressure and contribute to injury prevention [5,6,7,8,9,10]. Furthermore, suspended monorail transit systems have many advantages, including low manufacturing cost, short construction time and high driving safety and quality, which attracts much attention.…”
Section: Introductionmentioning
confidence: 99%
“…In more recent studies, it is reported that accident counts display an excess presence of zeros than would be expected from either a Poisson or a negative binomial distribution (Chen et al 2016;Dong et al 2016;Kumara & Chin 2003;Qin et al 2004). This raises the issue of finding a more suitable distribution.…”
Section: Introductionmentioning
confidence: 98%